PENGARUH KEPUASAN KOMPENSASI PADA PERILAKU MELAYANI DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN (StudiPadaKaryawan PDAM TirtoMoedalSemarang ) - Siti Napisah, 10.05.51.0030 (Students Journal of Economic and Management, 2015)
The aim of this study was to determine the influence of variables COMPENSATION SATISFACTION BEHAVIOUR SERVE against PERFORMANCE. Periods of research used in this study ranging from September 28 until October 23, 2014, with the object of research is the employe of PDAM Tirta Moedal Semarang. The sampling technique in this research is to use the entire employee population data or data collection method using a questionnaire by distributing questionnaires to the respondents in order to obtain information. The research objective was formulated to find answere whichis affect employee performance. Data were analyzed using normality test data for testing the regression model confounding variables or residuals have a normal distribution, the classical assumption of test multicoloniarity to test correlation between the independent variables, factor analysis to test the validity of the question items, Cronbach alpha for testing the reliability of the instrument, analysis regression, to be tested with a coefficient of determination (R Â²), F test and t test models to test and prove the partial effect of each independent variable. The results of the research are: (1) Compensation Satisfaction have the positive and significant influence on employee performance. (2) Compensation Satisfaction has a positive and significant impact on the behavior of serving. (3) Compensation Satisfaction has a positive and significant impact on employee performance through serving behavior. Keywords: variable Compensation Satisfaction, Serving Behavior and Performance